Internet-based remote laboratory / Norsyakila Jamaludin - Jamaludin, Norsyakila (2001)
This thesis describes the software development for Internet-Based Remote Laboratory. Current technology enables the remote access and control of laboratory equipment and instrument for real-time via Internet. This can be especially useful in engineering education; part time student and remote student can conduct laboratory experiment remotely. Such remote laboratory experiment method can also enable student to use expensive laboratory experiment, which is not usually available to students. This thesis also present a general method of creating a web-based Remote Laboratory experimentation, which enables Electrical Engineering students to control the real instrument through Internet and conduct oscilloscope experimentation remotely. The philosophy behind this remote laboratory is based on a client/server configuration.